Modern political analysis - Dahl, Robert Alan (New Jersey : Prentice Hall, 1991)
This classic introduction provides an analysis and description of democracy, political behavior, political evaluation, policy making and comparative political systems. Power and influence, pivotal features of the book, are depicted through concrete illustrations of people holding varying degrees of power. Thus, the reader is invited to enter imaginatively into the experiences of those people. Throughout, this inclusive volume offers all the basic concepts, ideas and tools necessary for the analysis of politics and puts ten types of political systems into perspective. Valuable charts and tables approximately 170 countries visually enhance the narrative.
Preface -- One. What is Politics? -- Two. Describing Influence -- Three. Interpreting Influence -- Four. Explaining and Appraising Influence -- Five. Political Systems: Similarities -- Six. Political Systems: Differences -- Seven. Differences: Polyarchies and Nonpolyarchies -- Eight. Polyarchies and Nonpolyarchies Explanation -- Nine. Political Men and Women -- Ten. Political Evaluation -- Eleven. Choosing Policies: Strategies of Inquiry and Decision -- Index.
Includes index.
Keywords: POWER (SOCIAL SCIENCES).; POLITICAL SCIENCE